1995
DOI: 10.1128/jb.177.11.3120-3127.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a cam repressor (CamR) for the cytochrome P-450cam hydroxylase operon on the Pseudomonas putida CAM plasmid

Abstract: The cytochrome P-450cam hydroxylase operon of Pseudomonas putida PpG1 (ATCC 17543) encodes proteins responsible for early steps of the degradation of D-camphor. Transcription of this operon is negatively controlled by the cam repressor (CamR), and the expression of camR is autoregulated. CamR was purified from Escherichia coli harboring an overproducing plasmid. The repressor forms a homodimer with a molecular mass of 40 kDa, as judged by sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
(17 reference statements)
2
28
0
Order By: Relevance
“…According to the data from the SPR experiments in this study, the K D of CmeR to P cmeABC is 88 Ϯ 2 nM, which is in the same range as that reported for EthR (K D ϭ 146 nM), another repressor of the TetR/CamR family (8). By contrast, the affinities of MexL and CamR to their corresponding target promoters were low, with K D values of 900 nM and 1,500 nM, respectively (1,5). However, the K D values of MexL and CamR were determined by gel mobility shift assays, instead of by SPR.…”
Section: Discussionmentioning
confidence: 72%
“…According to the data from the SPR experiments in this study, the K D of CmeR to P cmeABC is 88 Ϯ 2 nM, which is in the same range as that reported for EthR (K D ϭ 146 nM), another repressor of the TetR/CamR family (8). By contrast, the affinities of MexL and CamR to their corresponding target promoters were low, with K D values of 900 nM and 1,500 nM, respectively (1,5). However, the K D values of MexL and CamR were determined by gel mobility shift assays, instead of by SPR.…”
Section: Discussionmentioning
confidence: 72%
“…dation in Pseudomonas putida (42), TcmR, the repressor of the Streptomyces glaucescens tetracenomycin C resistance gene tcmA (43), and TetR (19). QacR appears to be unusual for this family of proteins in that expression of its own gene was not subject to autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, purified MexZ has been shown by gel-shift assay to bind with a DNA fragment from the mexZ-mexX intergenic promoter region (Matsuo et al, 2004). A computer-aided similarity search of MexZ has revealed that MexZ is a member of the TETR family of repressors (Aires et al, 1999;Westbrock-Wadman et al, 1999), which forms a homodimer for DNA binding (Aramaki et al, 1995;Grkovic et al, 2001;Hillen & Berens, 1994). We therefore hypothesized that MexZ represses the transcription of mexXY, except in the presence of an appropriate inducer molecule such as TET.…”
Section: Promotion Of Mexz Production By Tetracycline and Mexz Bindimentioning
confidence: 99%